2013
DOI: 10.1097/prs.0b013e3182729ff7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis for Apoptosis and Necrosis on Adipocytes, Stromal Vascular Fraction, and Adipose-Derived Stem Cells in Human Lipoaspirates after Liposuction

Abstract: Adipose-derived stem cells had a higher rate of apoptosis and necrosis than adipocytes. However, the extent of apoptosis and necrosis was significantly different among adipose-derived stem cell subpopulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…ASC viability is dependent on cell proliferation, which also was significantly reduced by Octenisept®. In contrast to apoptosis, which is a well-controlled form of cell death that may be inhibited by certain measures, Octenisept® induces necrosis, an irreversible and therefore more detrimental form of cell death (28, 29). Necrosis is followed by an inflammatory response, which may further perpetuate the critical condition of wound repair disorders (30).…”
Section: Discussionmentioning
confidence: 99%
“…ASC viability is dependent on cell proliferation, which also was significantly reduced by Octenisept®. In contrast to apoptosis, which is a well-controlled form of cell death that may be inhibited by certain measures, Octenisept® induces necrosis, an irreversible and therefore more detrimental form of cell death (28, 29). Necrosis is followed by an inflammatory response, which may further perpetuate the critical condition of wound repair disorders (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite promising clinical potential, a detailed understanding of the putative molecular mechanisms for ADSC-mediated reversal of RTX-injury remains elusive ( 36 , 44 , 57 ). Additionally, concerns have been raised that fat grafting following cancer treatment may enhance tumorigenesis in a former cancer bed ( 58 60 ). If fat grafting is to become a useful and validated clinical tool, these issues must be addressed.…”
Section: Biological Properties Of Fat Graft and Adscsmentioning
confidence: 99%
“…In contrast, Butala et al suggested that introduced ADSCs may recruit further stem cells, particularly from bone marrow ( 30 , 53 , 55 , 72 ). To enhance the relative ADSC abundance within fat grafts ( 44 , 58 , 72 , 73 ), Yoshimura et al proposed “cell-assisted lipotransfer enrichment” (Figure 2 ), by supplementing lipoaspirate with additional SVF ( 23 , 43 , 60 , 62 , 64 , 74 , 75 ). The SVF [comprised 10% ADSCs ( 45 , 46 , 65 , 67 )], is obtained from a component of lipoaspirate, surplus to the volume anticipated to be required to fill a known defect ( 30 ).…”
Section: Enhancing Fat Graft Take Using Adscsmentioning
confidence: 99%
“…ADSCs have now become the most studied adult stem cell and are thought to play a key role in the restorative, reconstructive and sustainable qualities of transferred fat 16 34–38…”
Section: Introductionmentioning
confidence: 99%